Takayasu’s arteritis with involvement of small cutaneous vessels - with regard to a clinical case - Ma. Cristina Fialho; Sara Castro; Sara Dias; Ricardo Veiga; Ana Ferreirinha; Emanuel Marques; Cândida Fernandes (Revista da Sociedade Portuguesa de Dermatologia e Venereologia)
Takayasu’s arteritis (TA) is a vasculitis that affects large vessels. Rarely, microcirculation is involved, sometimes with cutaneous manifestations. Inflammation of small vessels of the skin can present as erythema nodosum-like lesions and granulomatous cutaneous vasculitis, among others. We describe the case of a 29-year-old woman with a diagnosis of TA confirmed by angio-CT. She was referred to a dermatology appointment due to a skin condition characterized by centimetric, erythematous, painful, and nonulcerated nodules on the soles and inner edges of the feet. Clinical and analytical criteria of active disease were met, despite implemented corticotherapy. Cutaneous biopsy showed panniculitis and leukocytoclastic vasculitis. Autoimmune vasculitis and cryoglobulinemia panels were negative. Erythema nodosum-like subcutaneous nodules have been described in TA, possibly preceding other disease manifestations or as markers of disease activity. An early correlation with constitutional and cardiovascular symptoms may lead to earlier diagnosis and prompt control of disease activity.Takayasu’s arteritis (TA) is a vasculitis that affects large vessels. Rarely, microcirculation is involved, sometimes with cutaneous manifestations. Inflammation of small vessels of the skin can present as erythema nodosum-like lesions and granulomatous cutaneous vasculitis, among others. We describe the case of a 29-year-old woman with a diagnosis of TA confirmed by angio-CT. She was referred to a dermatology appointment due to a skin condition characterized by centimetric, erythematous, painful, and nonulcerated nodules on the soles and inner edges of the feet. Clinical and analytical criteria of active disease were met, despite implemented corticotherapy. Cutaneous biopsy showed panniculitis and leukocytoclastic vasculitis. Autoimmune vasculitis and cryoglobulinemia panels were negative. Erythema nodosum-like subcutaneous nodules have been described in TA, possibly preceding other disease manifestations or as markers of disease activity. An early correlation with constitutional and cardiovascular symptoms may lead to earlier diagnosis and prompt control of disease activity.